Experimental evaluation of stable long term operation of semiconductor magnetic sensors at ITER relevant environment. (30th June 2015) - Bolshakova, I.; Belyaev, S.; Bulavin, M.; Brudnyi, V.; Chekanov, V.; Coccorese, V.; Duran, I.; Gerasimov, S.; Holyaka, R.; Kargin, N.; Konopleva, R.; Kost, Ya.; et al.
Abstract: The paper deals with radiation resistant sensors and their associated measuring instrumentation developed in the course of R and D activities carried out in the framework of an international collaboration. The first trial tests of three-dimensional (3D) probes with Hall sensors have been performed in European tokamaks TORE SUPRA (2004) and JET (2005). Later in 2009 six sets of 3D probes were installed in JET and now continue to operate. The statistical analysis performed in 2014 on the basis of the JET database have demonstrated stable long term operation of all 18 sensors of 3D probes. The results of measurements conducted at the neutron fluxes of nuclear reactors have demonstrated the operability of the sensors up to high neutron fluences of F > 10 18 n ∙ cm −2 that exceeds the maximum one for the locations of steady state sensors in ITER over its total lifetime.